KUALITAS SPERMATOZOA SWIM UP KAMBING PERANAKAN ETAWAH HASIL PEMBEKUAN MENGGUNAKAN METODE VITRIFIKASI DENGAN PERSENTASE GLISEROL YANG BERBEDA - Saka Wahyu Hikamawan; Gatot Cipatadi; Sri Wahjuningsih (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2016)
The objective of this research was to examine the effect of glycerol addition in different percentage to quality of swim up spermatozoa from Etawah Grade buck that frozen with vitrification method. This research was carried out at Frozen Semen Laboratory, Sumbersekar, Faculty of Animal Husbandry, Brawijaya University from February 2016 to March 2016. This research design was experimental laboratory using completely randomized design and the data were analyzed using Analysis of Variance (ANOVA) one way pattern, followed by the multiple test Duncan. There were four treatments in this research (P0= Tris-Yolk + 0% Glycerol, P1= Tris-Yolk + 7% Glycerol, P2= Tris-Yolk + 14% Glycerol, P3= Tris – Yolk + 21% Glycerol). Each treatment consisted of ten replications. The results showed that addition of glycerol was significantly different (P<0,01) on the percentage of post thawing motility, viability, and total spermatozoa motility. It was concluded that addition of glycerol 7% gave the best result on spermatozoa quality. Keywords : swim up, glycerol, frozen semen, vitrification, post thawing motility